'Naming Whiteness': an inquiry into Lindy Chamberlain's Through my eyes and Australian nationalist discourses - P. Saywer (Law Text Culture, 1997)
On the day before Australia Day, in 1995, an article by Martin Flanagan (1995) entitled 'A Land Like No Other' appeared in The Age, Melbourne's well respected major daily newspaper, inquiring into Australian 'national identity' and questioning how Australian nationalism addresses issues of racial identity. Who are we?' Flanagan asks, 'and how is our culture defined?' In his attempt to answer these questions, he identifies the figures who have contributed to Australia's cultural identity. The two female exceptions to his list of male contributors are Cathy Freeman and Lindy Chamberlain.